Assessment of Awareness and Attitude Regarding Early Childhood Caries among Parents of Preschool Children Attending Pediatric Outpatient Department: A Cross-sectional Study - S. Deepak; Gaurav Mishra; Vinay Kumar Gupta; Sumit Kumar; Aman Rajput; Mohit Kumar Kanoujia (Journal of Indian Association of Public Health Dentistry)
Background: Early childhood caries (ECC) is a common chronic disease in young children, negatively impacting their health and development. The family environment, particularly parental knowledge, significantly influences children’s oral health. This study aims to evaluate ECC awareness and attitudes among parents of preschool children in Lucknow. Materials and Methods: A cross-sectional study with 400 participants was conducted using simple random sampling. Parents visiting the pediatrics department at a tertiary hospital in Lucknow were included. Data were collected through a self-structured questionnaire, validated through a pilot study (Cronbach’s α = 0.85, face validity 84%, content validity ratio 0.78). Awareness scores were analyzed using SPSS version 24, employing Chi-square, t-tests, ANOVA, and multivariate linear regression. Results: The sample consisted of 38.3% females and 61.8% males, with 35.5% from urban areas and 64.5% from rural areas. Awareness scores were higher in females (Mean = 8.65) than in males (Mean = 6.93) and higher in urban (Mean = 9.86) than rural areas (Mean = 6.45). Education level positively correlated with awareness (F = 10.797, P < 0.001), while income showed a complex relationship. Multivariate regression indicated that gender and education positively influenced awareness scores, whereas area and income had negative impacts, warranting further investigation. Conclusion: Parental awareness of ECC is significantly influenced by gender, education, and area. Educational interventions should target rural areas and parents with lower education levels to enhance oral health knowledge and practices.